Fatigue in patients with primary sclerosing cholangitis. - Björnsson, E; Simren, M; Olsson, R; Chapman, R (2004)
BACKGROUND: The occurrence of fatigue in primary sclerosing cholangitis (PSC), its impact on quality of life and the role of concomitant inflammatory bowel disease (IBD) and coexisting irritable bowel syndrome (IBS) is unexplored. METHODS: Ninety-three patients with PSC, associated with IBD in 80% of cases and 77 patients with IBD alone, were enrolled in the study. The patients completed the following questionnaires: the Fatigue Impact Scale (FIS), the Psychological General Well-Being Index (PGWB), the Gastrointestinal Symptom Rating Scale (GSRS), the Beck Depression Inventory (BDI) and diagnostic criteria for IBS. Questionnaire data were related to liver tests and the latest liver biopsy in the PSC patients. Two sex- and age matched controls from the general population (GP) were assigned to each PSC patient and these controls completed the FIS and the BDI. RESULTS: Total fatigue score did not differ significantly between patients with PSC and IBD alone. Median total fatigue score among GP subjects was 39 (13-72), which was higher than in PSC (19 (6-52) (P = 0.02)) and in IBD patients (19 (5-35) (P < 0.0001)). PGWB and GSRS scores did not differ between patients with PSC and IBD alone. Depression and general health (PGWB) were independent predictors for total fatigue score in PSC. No correlation was observed between fatigue in PSC and the severity of the liver disease. CONCLUSIONS: Fatigue in patients with PSC is related to depression but not to the severity of the liver disease. Both the PSC and IBD patients had lower total fatigue scores than subjects from the general population. This argues against fatigue as a specific symptom of PSC and IBD patients.